Short Axillary Vein and an Axillary Venous Ladder Formed by Basilic and Brachial Veins – An Anatomical and Clinical Perspective - Satheesha Nayak B,; Srinivasa RS,; Ashwini AP,; Naveen K,; Swamy RS,; Deepthinath R,; Surekha DS,; Prakashchandra S, (Faculty of Medicine, UKM Medical Centre, 2015)
Knowledge of anatomic variants of veins in the arm and axilla play a key role in planning of successful venous access. Possible anatomic variants of axillary vein, brachial vein and basilic vein and their clinical implications have been well described in the literature. We report a rare case of formation of a short axillary vein associated with complex venous communications between the basilic and brachial veins forming a venous ladder in the axilla, in formalin embalmed male cadaver. Axillary vein was formed in the upper part of the axilla by the fusion of basilic vein and unpaired brachial vein, and it was about 3cm in length. The higher-up confluence of basilic and brachial veins was also associated with presence of three communicating veins between the basilic and brachial veins in the axilla. Knowledge of reported venous variations is very useful during preoperative venous mapping and also for planning and execution of various surgical invasive procedures involving these veins.